2018
DOI: 10.1165/rcmb.2018-0004oc
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cigarette Smoke Exposure on the Lung Fibroblastic Response after Influenza Pneumonia

Abstract: Influenza viruses can result in significant lung injury with significant morbidity and mortality. In this study, we evaluated the impact of cigarette smoke (CS) exposure on the pulmonary fibroblastic response after influenza infection. We used a murine model in which animals were exposed to CS or room air and subsequently infected with H1N1 influenza virus. Inflammatory and fibrotic responses were measured at different time points after influenza infection. Primary fibroblasts were isolated from the lungs of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Similarly, Hong et al noted that, with H3N2 at 25 TCID50 with 3 month CS exposure, CS exposed mice had 100 fold higher live virus titers at 10 dpi vs. the no CS controls, suggesting viral clearance had been impeded [37]. Interestingly, Lee et al has shown, using PR8 IAV at 100 PFU per mouse with 2 weeks CS exposure, that early viral titers at three days post infection were higher in CS mice vs controls, but peak viral titers and post peak clearance for CS and controls were identical in contrast to previous studies [38]. While seemingly conflicting, we would assume that these conflicting clearance results are more potentially due to variability in IAV dose, CS exposure, and viral genotype rather than being in direct contradiction.…”
Section: How Does Cs Affect Immune Responses To Iav Pulmonary Insult?mentioning
confidence: 82%
See 2 more Smart Citations
“…Similarly, Hong et al noted that, with H3N2 at 25 TCID50 with 3 month CS exposure, CS exposed mice had 100 fold higher live virus titers at 10 dpi vs. the no CS controls, suggesting viral clearance had been impeded [37]. Interestingly, Lee et al has shown, using PR8 IAV at 100 PFU per mouse with 2 weeks CS exposure, that early viral titers at three days post infection were higher in CS mice vs controls, but peak viral titers and post peak clearance for CS and controls were identical in contrast to previous studies [38]. While seemingly conflicting, we would assume that these conflicting clearance results are more potentially due to variability in IAV dose, CS exposure, and viral genotype rather than being in direct contradiction.…”
Section: How Does Cs Affect Immune Responses To Iav Pulmonary Insult?mentioning
confidence: 82%
“…However, in cigarette mouse models, IAV infection results in worse disease outcomes compared to non-smoking controls. For example, CS exposure and subsequently infection typically will result in reduced weight gain post infection [34][35][36][37][38], increased lung remodeling (deposition of scar tissue replacing functional lung tissue) [39,40] and increased mortality [33,[35][36][37]41] compared to non-CS infected mice. Similarly, CS exposure in humans is shown to be associated with increased risk of influenza infections [4,42,43], increased risk of severe symptoms [4], and decreased efficacy of influenza vaccine [44,45].…”
Section: How Does Cs Affect Immune Responses To Iav Pulmonary Insult?mentioning
confidence: 99%
See 1 more Smart Citation
“…Comorbid chronic health conditions, including metabolic syndrome 39 , heart failure 40 and chronic obstructive pulmonary disease 41 , also increase an individual's risk of severe disease. Finally, environmental factors, such as cigarette smoke exposure, contribute to disease severity 42 , potentially as a result of alterations in epithelial and immune cell function 43 as well as in fibroblast repair responses to viral infection 44 .…”
Section: Global (Who Data)mentioning
confidence: 99%
“…Lung fibrosis was developed in some cases post-H1N1 influenza viral infection [ 60 ]. Chronic lung disease patients with frequent exacerbations of influenza infection subsequently developed fibrotic interstitial lung disease [ 61 ]. Following H1N1 influenza viral infection, an expansion of distal airway stem cells (DASC) expressing BC markers Trp63 and Krt5 assembled into nascent alveoli at sites of interstitial lung inflammation.…”
Section: Introductionmentioning
confidence: 99%